Bivalve Biodiversity in Ekas Waters as an Indicator of Aquatic Environmental Quality - Lalu Kinayung Purbajati; Ali Haris; Mukminah Mukminah; M. Harja Effendi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Bivalves are one of the aquatic organism groups that play an important role in maintaining the balance of aquatic ecosystems. This role makes bivalves essential not only in food webs but also in sustaining overall water quality. This study employed a quantitative descriptive approach using a purposive sampling method. Sampling was conducted using hand nets, forceps, 1 × 1 m quadrat frames, buckets, plastic containers, gastropod identification guides, a GPS device, a pH meter, millimeter block paper, and a camera. The collected data were analyzed using community structure indices, including the Shannon–Wiener diversity index, evenness index, species richness index, Simpson dominance index, and importance value index. These indices were then interpreted to describe the condition of the aquatic environment. The results of the bivalve community structure analysis showed that the Shannon–Wiener diversity index (H′ = 1.840) indicated a moderate level of diversity, accompanied by a high evenness index (E = 0.885) and a low Simpson dominance index (D = 0.174). This combination of values suggests a relatively even distribution of individuals among species, with no single species strongly dominating the community. Overall, these conditions indicate that the water quality at the study site can be classified as moderate to good, or lightly polluted, and remains capable of supporting the sustainability of various benthic species.